Sonophotocatalytic Degradation of Paracetamol in the Presence of Iron-doped Titanium Dioxide - Yap, Hui Cheng (2018)
In recent years, growing consideration has been given to the presence of emerging pollutants (EPs) in water sources. EPs such as paracetamol possess characteristics of bioaccumulative, persistent and highly soluble in water. However, conventional treatment methods such as physical adsorption, chlorination and activated sludge may ineffective to remove and degrade the paracetamol. Therefore, in this study, sonophotocatalytic degradation has been proposed as an advance hybrid method to accelerate the process of paracetamol degradation. Titanium dioxide (TiO2) and iron-doped TiO2 (Fedoped TiO2) particles were synthesised by sol-gel method using tetrabutyl orthotitanate and iron (III) nonahydrate as titanium and iron sources, respectively. Various Fe dopant concentrations (1, 3, 5 and 10 wt%) and calcination temperatures (200, 400, 600 and 800 °C) of Fe-doped TiO2 were prepared. Characterisations of samples were performed using FESEM-EDX, XRD, XPS and nitrogen adsorption-desorption analysis to examine the surface morphology, elemental composition, phase structure, chemical states and surface analysis. 3% Fe-doped TiO2-600 catalyst showed the highest catalytic activity due to the presence of Fe dopant in optimum amount and mixed anatase-rutile phase. The effect of operating parameters such as energy